AKUNTABILITAS DAN TRANSPARANSI PENGGALANGAN DANA DONASI SECARA ONLINE MELALUI PLATFORM KITABISA.COM - Irene Margaretha Warouw; Yohanes Harimurti (Universitas Katolik Widya Mandala Surabaya, 2024)
The aim of this research is to explore the meaning of accountability and transparency by parties involved in online fundraising activities through the Kitabisa.com platform and then evaluate accountability and transparency practices on the platform. This research uses a qualitative approach by exploring data from informants who act as fundraisers, donors and beneficiaries. This research found different perspectives on the meaning of accountability regarding who should accountability be given to? Platform providers interpret accountability as being given to donors as providers of resources. Fundraisers interpret accountability to God as the principal, while donors interpret the primary accountability to the beneficiaries (downward accountability). On the other hand, beneficiaries need transparency more than accountability.